EFEKTIVITAS BALIHO DALAM MENDUKUNG KESIAPSIAGAAN BENCANA DI KABUPATEN WASIOR PAPUA BARAT - Delly Afrindasari; Mohamad F. N. Aulady (Jurnal Manajemen Bencana (JMB), 2023)
Flash floods are inundations aused by a river discharge that suddenly and quickly exceeds the flow capacity. This incident occurred in the eastern part of Indonesia, specifically in Wasior Regency, West Papua, in 2010. It was caused by the arrival of intense rain a few days earlier and finally brought fatal, consequoences to the river overflow in Wasior. These conditions became the parameters for research to offer a structural mitigation program during the pre-disaster period by placing billboards at flash flood-prone points in Wasior containing disaster mitigation materials. Billboard was chosen as the medium because the information conveyed is more easily accessible to the public. The researchers distributed questionnaires to 34 respondents as research instruments with pretest dan posttest classes. Resoondents came from the Manggurai village community living around the Manggurai river. The results of the analysis showed that the knowledge of the people who were respondents in this study through the pretest and posttest was considered better. The posttest got 53.14%, while the pretest obtained 46.67%. Meanwhile, a in the t-test (sig < 5%) indicated that billboards were media in Wasior Regency for disaster preparadness.